Analisis Jual Beli Tanah Tanpa Sertifikat Perspektif Maslahah Mursalah - Oshin, Oshin (Fakultas Syariah IAIN Kendari, 2024)
The study aims to examine the practice of buying and selling uncertified plot land in Maperaha Village and analyze it from the perspective of Maslahah Mursalah. The research employs a normative-empirical approach, identified through case study and conceptual methods. The subjects of the study include 12 informants, consisting of community leaders, the village head and secretary, land office staff, sellers, and buyers. Data were collected through observation, interviews, and documentation.Based on the findings, the study concludes the following: First, the practice of buying and selling uncertified plot land in Maperaha Village is conducted without adherence to village government procedures. Transactions are carried out directly between sellers and buyers without legal verification, witnesses, or a village-issued sales certificate. This practice is preferred because it is fast and incurs no additional costs.Second, the analysis based on Maslahah Mursalah reveals that among six cases, four are inconsistent with the principles of maslahah due to their potential to cause disputes and the absence of formal evidence. However, two cases align with the principles of maslahah, as the transactions were conducted with clarity and honesty.Kata Kunci: Jual Beli, Tanah Tanpa Sertifikat, Maslahah Mursalah